A comparative morphological and histological study of the gastrointestinal tract of four insectivorous bat species: Asellia tridens, Chaerephon pumilus, Nycteris thebaica, Rhinopoma hardwickii. (22nd May 2019) - Aylward, Mikal; Beselaar, Leandrie C.; Alagaili, Abdulaziz N.; Amor, Nabil M. S.; Mohammed, Osama B.; Kotzé, Sanet H.
Abstract: Various studies address the morphology of the gastrointestinal tracts (GITs) of insectivorous bat species. However, detailed morphometric studies including mucin histochemistry are scarce. This study compares various GIT measurements as well as the quantification of intestinal mucin secreting cells in four insectivorous bat species representing four different families of Chiroptera. Alcian blue/Periodic acid Schiff's stain was used to differentiate between acid and neutral mucin‐secreting cells while the Aldehyde fuchsin/Alcian blue stain further differentiated between two acid mucins, namely sialo‐, and sulphomucins. The number of cells was quantified and statistically analysed. All species had a simple GIT morphology represented by a simple, completely glandular stomach and the absence of a cecum. The exception was R. hardwickii, where a small cecum was observed which had histological mucosal features of both the small and large intestine. In R.hardwickii, distal to the cecum, typical colonic mucosal features such as the absence of villi and an abundance of goblet cells were observed. In all four species, the total number of goblet cells increased from the proximal to the distal intestinal regions. Mixed (acid and neutral) mucins dominated the entire GIT of all species. Neutral mucin‐secreting cells were observed in the gastric pylorus and proximal intestinal regions in all species. Brunner's glands stained positive for neutral mucins. Exclusively acid mucin‐secreting cells were seen in the distal intestinal regions of all species except N. thebaica . Sulphomucin‐secreting cells were the most prominent acid mucin cell‐type towards the distal intestine. The distribution of different mucin secreting cells indirectly provides information regarding the quality of the intestinal biofilm in the species studied. Abstract : Insectivorous bats have a simple gastrointestinal morphology, with only R. hardwickii having a cecum. Distribution of mainly mixed (acid and neutral) and sulphated mucins provide insight into the quality of the intestinal biofilm.